DESTINATION IMAGE OF BALI BASED ON THE PUSH MOTIVATIONAL FACTORS, IDENTITY AND DESTINATION CREATIONS IN THE PERSPECTIVE OF FOREIGN SENIOR TOURIST* - I Gusti Bagus Rai Utama (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2016)
The strength of the senior traveler segment is the high purchasing power the length of stay in a destination, making this market segment increasingly important in present and future. Consequently, this research aims to establish a model of motivation and its relationship with the image of Bali as an international tourism destination, especially from the perspective of senior tourists. This research employed survey method and utilized a combination of quantitative and qualitative analytical techniques. Factor analysis condensed various indicators into several key indicators to form a model with goodness of fit. Indicators representing push motivation variable include the improvement of health/fitness and the drive to perform physical exercise. Indicators representing destination identity variable include the culture and nature of Bali. Indicators representing destination creation variable include the service quality of travel agencies and service quality of travel guides. Indicators representing destination image variable include the image of cultural uniqueness and holiday atmosphere of Bali. The survey in this study involved 400 respondents of senior tourists, exclusively only foreign nationals. Goodness of fit is affirmed on the results of the analysis model, which answered the hypothesis that push motivation and destination creation affect destination images.